Mikalojus Konstantinas Čiurlionis’s Socio-Cultural Connections and Professional Self-Realisation in Lithuania - Gaidauskienė, Nida (Colloquia, 2021)
In 1907–1909, Mikalojus Konstantinas Čiurlionis worked with seven national societies active in Lithuania: Lithuanian Art Society, Amateur Music and Theatre Society “Vilniaus Kanklės”, Lithuanian Association “Rūta” in Vilnius, Music and Theatre Society “Daina” in Kaunas, Lithuanian Scientific Society, Lithuanian Mutual Aid Society of Vilnius, and Charitable Society for Pupils and Students “Žiburėlis”. He was a member of the formerthree organizations. The Lithuanian Art Society was the main platform for Čiurlionis’s professional and social self-realisation. He served as its vice-chair and from September 1907 to September 1909 stood in for its chair, Antanas Žmuidzinavičius. He organised the Second Lithuanian Art Exhibition. On Čiurlionis initiative, the music section was established at the Society. Together with his colleagues, he organized a competition for Lithuanian composers; he also envisaged a periodical of music, art, and literature.The article discusses the question of the affiliation with the Lithuanian Vilnius Choir led by Čiurlionis. The research has revealed that Čiurlionis conducted a united choir consisting of the singers from the Lithuanian Mutual Aid Society of Vilnius and “Vilniaus Kanklės”. His participation in two soirees organised by “Žiburėlis”, quite favourable reviews of his artworks written by the liberals, and the principled criticism by the conservative cleric Aleksandras Dambrauskas (nom de plume Adomas Jakštas) demonstrate that Čiurlionis found it easier to work with democratic left-wing cultural figures. In June of 1909, Čiurlionis’s concert and the design of the curtain on the premises of the Lithuanian Association “Rūta” were associated with Andrius Domaševičius and Kipras Petrauskas. In his letter, Čiurlionis called himself “progressive.” It was uncharacteristic to indicate one’s party affiliation; in Čiurlionis’s case, it meant to be of liberal orientation. However, it was precisely because of his “leftist” views that the Educational Society “Aušra” deemed his membership unreliable. On July 11, 1909, Čiurlionis was nominated to the commission to collect songs for the Lithuanian Scientific Society. Unfortunately, the illness that manifested itself in December of 1909 prevented the composer from carrying out the work.
Keywords: Mikalojus Konstantinas Čiurlionis; Lithuanian Art Society; Lithuanian Scientific Society; Lithuanian Mutual Aid Society of Vilnius; “Vilniaus Kanklės”; “Žiburėlis”; “Rūta”; “Daina”